Hero's Journey Study of Lucy Pevensie: Voyage of the Dawn Treader (2010) Film - Gading Oryza Sativa Putri (LITERA KULTURA : Journal of Literary and Cultural Studies, 2026)
In The Voyage of the Dawn Treader (2010) film, Lucy Pevensie is going through an adventure to find the Seven Lords that lost and she must face several challenges such as monsters and villains, but her actual challenge are actually the physically invisible things which was the challenge between her and her internal side that related to her transformation and the acceptance of her own identity. Combined with the framework of the Hero’s Journey from Campbell, this study are based on three main phases: Departure, Initiation, and Return related to Lucy’s character development towards her main victory to recognize her own value and her identity. Thus, this study aims to analyze Lucy’s journey cycle and her character development process through the Hero’s Journey framework by Joseph Campbell.